Group Counseling with Contract-Behaviour Technique to Reduce Academic Procrastination in High School Students - Isnanda, Hafiski Luthfinuddin (Darul Ilmi Bina Insan Foundation, 2025)
Academic procrastination negatively impacts students' performance and psychological well-being. This study aimed to examine the effectiveness of group counseling using the Behaviour-Contract technique to reduce academic procrastination among high school students. The research involved six students from Class X-7 at Senior High School 3 Kediri and was conducted using a Classroom Action Research (CAR) model over two cycles. The intervention combined behavioral contracts, peer support, and positive reinforcement within structured counseling sessions. Data were collected through observation sheets, behavior contracts, and the Pure Procrastination Scale (PPS), then analyzed using Repeated Measures ANOVA. Results indicated a significant reduction in procrastination levels across both cycles. Improvements were also noted in students’ time management, self-regulation, and academic responsibility. Group interaction and reflective discussion enhanced motivation and engagement. These findings suggest that the Behaviour-Contract technique in group counseling is an effective method for reducing academic procrastination and fostering positive behavioral change in students